Coaching efficacy research: learning from the past and looking to the future - Boardley, I. D. (International Review of Sport and Exercise Psychology, 2018)
Coaching efficacy (CE) represents the extent to which coaches believe they have the capacity to affect the learning and performance of their athletes, and the CE model details antecedents, dimensions and outcomes of CE. Based around the CE model, the present paper had two main aims. First, to present a comprehensive and critical review of the research underpinned by the CE model. Studies were categorised by whether they investigated antecedents, outcomes or athletes` perceptions of their coach. Twenty-one published studies were identified for the review. Overall the review provides support for the main tenets of the CE model, with researchers establishing links between CE and many of the antecedents and outcomes proposed in the model. The second aim was to assimilate findings from the review, limitations in the CE model and relevant conceptual models to present a revised CE model. Whilst retaining the essence of the original model, the revised model also incorporates explicit processes linking coach beliefs and athlete perceptions, antecedents of athlete perceptions and an intrarelationship source of CE. It also incorporates specific categories of coach behaviour and athlete-/team-level outcomes. The paper concludes by identifying limitations in the literature and review, and by proposing key directions for future research.